Comparative humoral response of mRNA and inactivated vaccines against COVID-19 in healthy adults aged 60 years and older - Güvenir, Meryem; Yürüker, Özel; Yetkin, Osman; Süer, Kaya; Otlu, Barış (The Journal of Infection in Developing Countries, 2023)
Introduction: A vaccine against coronavirus disease 2019 (COVID-19) is critically needed for older adults because of the increased morbidity and mortality rates. Methodology: In this prospective study, we analysed the titre magnitude of the IgG antibodies directed against the SARS-CoV-2 Spike Protein S1 (S1-RBD) antigen in both CoronaVac and Pfizer-BioNTech groups. The samples were tested to detect antibodies that bind to the receptor-binding domain of the spike protein of SARS-CoV-2 using the Enzyme-Linked Immunosorbent Assay (ELISA) technique with SARS-CoV-2 IgG II Quant. The cut-off value was > 50 AU/mL. GraphPad Prism software was used. Statistical significance was defined at p < 0.05. Results: The CoronaVac group (12 females, 13 males) had a mean age of 69.64 ± 1.38 years. The Pfizer-BioNTech group (13 males, 12 females) had a mean age of 72.36 ± 1.44 years. The anti- S1-RBD titre decrease rate from the 1st to the 3rd month for CoronaVac and Pfizer-BioNTech groups was 74.31% and 86.48%, respectively. There was no statistically significant difference in the antibody titre between the 1st month and 3rd month for the CoronaVac group. However, there was a significant difference between the 1st and 3rd month in the Pfizer-BioNTech group. In addition, there was no statistically significant difference in the genders between the 1st and 3rd month of the antibody titres for both the CoronaVac Pfizer-BioNTech group. Conclusions: The levels of anti-S1-RBD, the preliminary outcome data of our study, represents one piece of the puzzle of humoral response and duration of vaccination protection.